Utilization of Gambier Leaves as Foot Lotion for Diabetics to Increase Community Income in The Limau Manis, Village, Padang, West Sumatra: Pemanfatan Daun Gambir Sebagai Lotion Kaki Pada Penderita Diabetes Untuk Meningkatkan Pendapatan Masyarakat di Kelurahan Limau Manis, Padang, Sumatera Barat - Hasanah, Uswatul; Suci Nasution, Embun; Fajar Putra, Adika (Universitas Haji Sumatera Utara, 2025)
Limau Manis is one of the villages located on Jalan Bandes, Pauh subdistrict, Padang city, West Sumatra province, Indonesia. Limau Manis village has a special problem, namely the lack of health training and the utilization of natural herbs of West Sumatra, namely gambier. This community service aims to provide education on the branding of the pharmacist, diabetes and its prevention, the use of gambier as diabetic’s foot lotion and workshops to make the product, marketing and business plans of a product. This community service conducted on July 12, 2024 with a modified Community Based Interactive Approach (CBIA) method. This activity is divided into 3 stages, namely the pre-implementation stage, the implementation stage, and the monitoring and evaluation stage. The diabetes’s foot lotion formula consists of gambier leaf extract, stearic acid, cera alba, nipagin, nipasol, paraffin liquid, glycerin, triethanolamine, corrigen odoris, and aquadest. Stability tests conducted on diabetes foot lotion for 6 cycles included organoleptic test, homogeneity test, pH test, spreadability test, and adhesion test. The result, distinctive aroma, brownish yellow color, and creamy shape, homogeneous, pH is 6.1 with spreadability 5.2-7 cm and the adhesion test >1 second. It no irritation on the hands of volunteers and met the requirements of the moisture test. The participants were representatives of farmers, housewives, Integrated Healthcare Center staff, youth organizations, and the community actively who were involved during the activity. The comunnity service using the CBA method can increase participans’ knowledge and skill by 77% obtain from pre-test and post-test.